Fourier transform convolution proof

  • Thread starter mcheung4
  • Start date
  • #1
22
0

Homework Statement



Let FT(f) = Fourier transform of f, (f*g)(x) = convolution of f and g.
Given FT(f*g) = FT(f)FT(g), the first part of the convolution theorem, show that FT[fg] = [FT(f)*FT(g)]/2pi.


Homework Equations



Duality: FT2f(x) = (2pi)f(-x)

Convolution: (f*g)(x) = ∫f(u)g(x-u)du


The Attempt at a Solution



FT(f*g) = FT(f)FT(g)
FT2(f*g) = FT[FT(f)FT(g)]
LHS = FT2(f*g)(x) = (2pi)(f*g)(-x) (by duality) =(2pi)∫f(u)g(-x-u)du (by convolution) = (2pi)∫{[FT2f(-u)][FT2g(x+u)]}/(2pi)2 du
implying that RHS = FT[FT(f)FT(g)] = (1/2pi)∫FT[FT(f(-u))]FT[FT(g(x+u))] du ≠ FT[fg] = [FT(f)*FT(g)]/2pi

Where did I go wrong?

Thanks!
 

Answers and Replies

  • #2
vela
Staff Emeritus
Science Advisor
Homework Helper
Education Advisor
14,756
1,354
Try letting f = FT(F) and g=FT(G). Then evaluate FT2(f*g) and FT[FT(f)FT(g)] separately and show they are equal.
 

Related Threads on Fourier transform convolution proof

  • Last Post
Replies
12
Views
686
  • Last Post
2
Replies
25
Views
2K
Replies
1
Views
2K
Replies
2
Views
862
Replies
2
Views
985
Replies
5
Views
770
Replies
1
Views
603
Replies
3
Views
2K
  • Last Post
Replies
6
Views
3K
Replies
1
Views
1K
Top